Biophysical Causality and Environmental Preference Elicitation: Evaluating the Validity of Welfare Analysis over Intermediate Outcomes. (19th October 2016) - Johnston, Robert J.; Schultz, Eric T.; Segerson, Kathleen; Besedin, Elena Y.; Ramachandran, Mahesh
Abstract : Stated preference scenarios often describe outcomes to be valued in terms of intermediate biophysical processes or ecosystem services with indirect utility effects, rather than in terms of final, directly welfare‐relevant consequences. This article evaluates whether valid welfare estimates can emerge from this practice. We begin with a theoretical model demonstrating conditions under which stated preference scenarios that include intermediate outcomes will elicit welfare estimates identical to those from parallel scenarios that include associated final outcomes (i.e., convergent validity will hold). The model demonstrates that a necessary condition for convergent validity is the ability of respondents to correctly predict biophysical production functions linking intermediate to final outcomes. Hypotheses from the theoretical model are then evaluated empirically using an application of choice experiments to migratory fish restoration in the U.S. state of Rhode Island. Empirical results are mixed but generally reject convergent validity; welfare estimates are not robust to the use of an intermediate outcome in lieu of a related final outcome in stated preference scenarios, as predicted by theory. Results of the analysis suggest that greater attention should be given to the reliability of welfare estimation when final outcomes cannot be quantified.